Multi-Word Expressions in Jordanian Arabic: A Socio-Pragmatic Study of Idioms and Proverbs - Alarsan, Falah; Khan, Tariq (International Journal of Language and Literary Studies, 2025)
The primary aim of this research endeavour is to conduct a thorough investigation, translation, and transliteration of multi-word expressions (MWEs) commonly found within the Arabic language and Jordan's cultural landscape, with a particular focus on idiomatic expressions and proverbs. In the context of Jordanian Arabic (JA), similar to various other linguistic frameworks, these MWEs occupy a pivotal position in the fabric of everyday discourse, proficiently encapsulating complex cultural meanings in a manner that is both succinct and impactful. The linguistic richness of Jordanian Arabic is highlighted by its diverse array of traditional idioms and proverbs, which frequently serve to distil profound cultural insights that reflect the values, beliefs, and historical narratives inherent to the Jordanian populace. The regular use of these expressions in casual conversation serves not only as a means of communication but also as a repository of cultural significance, embodying the essence of communal identity. This study aims to shed light on a critical yet often overlooked aspect of language use: the relatively infrequent application of certain idioms and proverbs can obscure their deeper meanings. Expressions that are not widely employed can often carry connotations that diverge considerably from their straightforward translations, revealing intricate layers of interpretation that are profoundly influenced by the surrounding cultural context. To elucidate this phenomenon, the research will methodically distinguish between the direct, interlingual meanings of these expressions and their connotative, culturally informed implications. Through this analytical lens, the study aims to deepen the readers' understanding of how culturally embedded concepts not only affect interpretations but also shape interpersonal relationships. This scholarly exploration emphasises the complex relationship between language and culture, illustrating that the richness inherent in the idiomatic and proverbial expressions of JA goes beyond mere vocabulary; it also offers insights into the collective wisdom and outlook of the Jordanian people. Ultimately, this research aspires to provide a comprehensive examination of MWEs of Jordanian Arabic, unravelling the significant implications these expressions hold in day-to-day communication and the articulation of cultural identity. Such an inquiry underscores the imperative to recognise idioms and proverbs not solely as structural and linguistic constructs, but as elements of socio-pragmatics and a multifaceted cultural heritage, seeking conservation and scholarly engagement.